Impact of didactic communication in enhancing learning and integration of meaningful content - Renard, María (Base Diseño e Innovación, 2016)
The subject that originates this article is the need to enable learning through didactic communication as a vehicle for meaningful experiences. The subject will be discussed in the framework of three matters: (i) what does the term didactic communication mean, (ii) Chile as a receiver of information, and (iii) the role of design in enhancing learning and meaningful experiences, with action-oriented recommendations. How do we achieve a new message to be recognized by a receiver? How do we motivate him and draw his attention to give meaning to the experience, so that he can make use of the content of this new message in his life? We propose three dimensions from where to address this: (i) technical dimension: where everything related to the fidelity of the message develops; (ii) semiotic and semantic dimension: where the meaning and interpretation that the receptor gives and makes of a message is addresses; and (iii) pragmatic dimension: where the subject of communication focuses on the consequences of the expected human behavior, also referred as, the didactic performance of the message. To exemplify this argument we expose three cases: discovering with you (acompañándote a descubrir), project for Clínica Las Condes Pediatric Division, and Oruam, the young magician.
Keywords: communication; didactic; meaningful learning